The identification of microrna signatures associated with glycaemic control and pregnancy outcomes in pregnancies complicated by Type 1, Type 2, and gestational diabetes mellitus - Pheiffer, Carmen (University of Pretoria, 2024)
Thesis (PhD (Reproductive Biology))--University of Pretoria, 2024.